2017
DOI: 10.1111/mec.14066
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and adaptation of malaria parasites on the edge of endemic distribution

Abstract: To determine whether the major human malaria parasite Plasmodium falciparum exhibits fragmented population structure or local adaptation at the northern limit of its African distribution where the dry Sahel zone meets the Sahara, samples were collected from diverse locations within Mauritania over a range of ~1000 km. Microsatellite genotypes were obtained for 203 clinical infection samples from eight locations, and Illumina paired‐end sequences were obtained to yield high coverage genomewide single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
(121 reference statements)
2
30
3
Order By: Relevance
“…Kobeni is the only sentinel site in Mauritania where studies on malaria epidemiology have been conducted regularly by several research teams over the past 20 years [2,7,9,[24][25][26][27][28][29][30][31][32][33]. Kobeni is situated within the 'heart' of area of seasonal but intense malaria transmission in Mauritania.…”
Section: Discussionmentioning
confidence: 99%
“…Kobeni is the only sentinel site in Mauritania where studies on malaria epidemiology have been conducted regularly by several research teams over the past 20 years [2,7,9,[24][25][26][27][28][29][30][31][32][33]. Kobeni is situated within the 'heart' of area of seasonal but intense malaria transmission in Mauritania.…”
Section: Discussionmentioning
confidence: 99%
“…28 The data have also been used to study gene deletions that cause failure of rapid diagnostic tests 29 ; to characterise genetic variation in malaria vaccine antigens 30,31 ; to screen for new vaccine candidates 32 ; to investigate specific host-parasite interactions 33,34 ; and to describe the evolutionary adaptation and diversification of local parasite populations. 7,9,12,[35][36][37][38][39][40] The Pf Community Project data also provide an important resource for developing and testing new analytical and computational methods. A key area of methods development is quantification of within-host diversity 7,[41][42][43][44][45][46] , estimation of inbreeding 7,47 , and deconvolution of mixed infections into individual strains.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this high level of genetic diversity resulting from non-synonymous nucleotide and amino acid substitutions observed, there remained a shared gene pool between the two sites that resulted in a largely homogeneous parasite population. Over the sampled range of 784.4 km kilometers between the two sites, there was gene ow between the local populations of P. falciparum based on Pfcsp sequence analysis, with pairwise index of differentiation (Fst) being less than 0.05 [33]. Principal component analysis further con rmed the lack of population structure or genetic isolation.…”
Section: Discussionmentioning
confidence: 93%
“…Principal component analysis further con rmed the lack of population structure or genetic isolation. Previous studies have indicated that human population mixing is likely to cause gene ow of P. falciparum parasites [33,34]. Despite the ecological and epidemiological diversity between the 2 sites, human movement between the two sites is signi cant and could be accounting for Pfcsp gene ow within Country.…”
Section: Discussionmentioning
confidence: 99%